On-stack two-dimensional conversion of MoS2 into MoO3. (29th November 2016) - Ko, Taeg Yeoung; Jeong, Areum; Kim, Wontaek; Lee, Jinhwan; Kim, Youngchan; Lee, Jung Eun; Ryu, Gyeong Hee; Park, Kwanghee; Kim, Dogyeong; Lee, Zonghoon; Lee, Min Hyung; Lee, Changgu; et al.
Abstract: Chemical transformation of existing two-dimensional (2D) materials can be crucial in further expanding the 2D crystal palette required to realize various functional heterostructures. In this work, we demonstrate a 2D 'on-stack' chemical conversion of single-layer crystalline MoS2 into MoO3 with a precise layer control that enables truly 2D MoO3 and MoO3 /MoS2 heterostructures. To minimize perturbation of the 2D morphology, a nonthermal oxidation using O2 plasma was employed. The early stage of the reaction was characterized by a defect-induced Raman peak, drastic quenching of photoluminescence (PL) signals and sub-nm protrusions in atomic force microscopy images. As the reaction proceeded from the uppermost layer to the buried layers, PL and optical second harmonic generation signals showed characteristic modulations revealing a layer-by-layer conversion. The plasma-generated 2D oxides, confirmed as MoO3 by x-ray photoelectron spectroscopy, were found to be amorphous but extremely flat with a surface roughness of 0.18 nm, comparable to that of 1L MoS2 . The rate of oxidation quantified by Raman spectroscopy decreased very rapidly for buried sulfide layers due to protection by the surface 2D oxides, exhibiting a pseudo-self-limiting behavior. As exemplified in this work, various on-stack chemical transformations can be applied to other 2D materials in forming otherwise unobtainable materials and complex heterostructures, thus expanding the palette of 2D material building blocks.